Uso de geoprocessamento para caracterização dos aspectos físicos, uso da terra e diagnóstico ambiental no município de Campina Do Monte Alegre (SP). - Carvalho, Giovana Costa (Universidade Federal de São Carlos, 2023)
The purpose of this research was to employ geoprocessing to analyze the physical aspects and land use to diagnose the environment in areas of permanent preservation (APPs) located in the municipality of Campina do Monte Alegre (SP). The study comprises the following stages: initially, the collection of data relating to the area under study, including planialtimetric maps (scale 1:10,000) and remote sensing products. Then the data was processed, using QGIS 3.32 software, detailing the physical aspects, the land use, in addition to demarcating and qualifying APPs in accordance with Law 12,651/2012. The final environmental diagnosis, overlapping the areas covered with native vegetation current with permanent preservation areas, it was found that the southern region of The municipality presents greater vulnerability with 39% deforested. Confirming thus, the need to recover native vegetation on site.
Geoprocessing to characterize aspects physical, land use and environmental diagnosis in the municipality of Campina do Monte Alegre (SP).
Keywords: Avaliação ambiental; SIG; APP; Environmental assessment; GIS; PPA; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::METODOS E TECNICAS DO PLANEJAMENTO URBANO E REGIONAL